Descriptions of malware and viruses, which are made with the help of cybercrime (Journal of actual problems of jurisprudence, 2018)
The article describes the types of viruses and programs that are used to attack information ofnetworks and systems. The characteristics of each of them are given here as well.However, laboratory researches presented in this article giving necessary information of spreading viral programsin the world. There is an analysis of the necessaryresearches for Kazakhstan. The author considers thatit is one of the most urgent problems of modern society.Key words: information networks, malware, types of viruses, information system, cybercrime.